2021
DOI: 10.3390/healthcare9030315
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Comparation of Extra-Short (4 mm) and Long (>8 mm) Dental Implants Placed in Mandibular Bone: A Systematic Review and Metanalysis

Abstract: This systematic review (SR) aimed to evaluate implant survival rate, marginal bone loss (MBL), and biological/prosthetic complications of extra-short 4 mm dental implants. An electronic search without language or date restrictions was performed in five databases and in gray literature for articles published until August 2020. Prospective cohort studies and randomized clinical trials (RCTs) that evaluated the clinical performance of extra-short 4 mm dental implants were included. Studies were independently asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 39 publications
(18 reference statements)
0
2
0
Order By: Relevance
“…Nonetheless, the techniques mentioned are often associated with high risk of surgical morbidity, high cost, excessive duration of treatment, low patient acceptance and incidence of post-operative surgical complication [5,6,7]. Apart from these techniques, short dental implants is one of the viable treatment options that can be considered as the most minimally invasive treatment in comparison to other treatment approach and modalities [8].…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, the techniques mentioned are often associated with high risk of surgical morbidity, high cost, excessive duration of treatment, low patient acceptance and incidence of post-operative surgical complication [5,6,7]. Apart from these techniques, short dental implants is one of the viable treatment options that can be considered as the most minimally invasive treatment in comparison to other treatment approach and modalities [8].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, surface functionalization and the introduction of implant threads (increasing the surface areas) has been described to transform occlusal stresses into more desirable and tolerable compressive forces at the implant-bone interface [140]. The length of the implants is also an important attribute to consider, when assessing the distribution of stresses, bone resorption and implant survival rates, as many clinical reports have shown that extra-short and short implants have lower success rates and higher bone resorption [141]; this was confirmed by the meta-analysis of Fernandes et al, which included randomized controlled trials (RCTs), and assessed data at one-year-, three-year-, five-year-and eight-year follow-ups [142]. Therefore, in the context of our study, it would be worthwhile to assess whether a difference exists in the modulating effect on bone mechanical properties after implant placement, involving implants of different length, diameter and surface properties.…”
Section: Discussionmentioning
confidence: 99%